XÁC ĐỊNH ĐƯỜNG CONG TĂNG TRƯỞNG TỐI ƯU CỦA TẾ BÀO ĐƠN LAN HỒ ĐIỆP (PHALAENOPSIS AMABILIS) TRONG NUÔI CẤY HUYỀN PHÙ TẾ BÀO - Trịnh Thị Lan Anh, Nguyễn Quốc Hiệu, Đặng Hòa Thuận, Lê Kim Cương , Hồ Thanh Tâm, (2023)
12(1)